Comprehensive collection of genes and comparative analysis of full-length transcriptome sequences from Japanese larch (Larix kaempferi) and Kuril larch (Larix gmelinii var. japonica) - Kentaro Mishima; Hideki Hirakawa; Taiichi Iki; Yoko Fukuda; Tomonori Hirao; Akira Tamura; Makoto Takahashi (BMC Plant Biology, 2022)
Abstract Background Japanese larch (Larix kaempferi) is an economically important deciduous conifer species that grows in cool-temperate forests and is endemic to Japan. Kuril larch (L. gmelinii var. japonica) is a variety of Dahurian larch that is naturally distributed in the Kuril Islands and Sakhalin. The hybrid larch (L. gmelinii var. japonica × L. kaempferi) exhibits heterosis, which manifests as rapid juvenile growth and high resistance to vole grazing. Since these superior characteristics have been valued by forestry managers, the hybrid larch is one of the most important plantation species in Hokkaido. To accelerate molecular breeding in these species, we collected and compared full-length cDNA isoforms (Iso-Seq) and RNA-Seq short-read, and merged them to construct candidate gene as reference for both Larix species. To validate the results, candidate protein-coding genes (ORFs) related to some flowering signal-related genes were screened from the reference sequences, and the phylogenetic relationship with closely related species was elucidated. Results Using the isoform sequencing of PacBio RS ll and the de novo assembly of RNA-Seq short-read sequences, we identified 50,690 and 38,684 ORFs in Japanese larch and Kuril larch, respectively. BUSCO completeness values were 90.5% and 92.1% in the Japanese and Kuril larches, respectively. After comparing the collected ORFs from the two larch species, a total of 19,813 clusters, comprising 22,571 Japanese larch ORFs and 22,667 Kuril larch ORFs, were contained in the intersection of the Venn diagram. In addition, we screened several ORFs related to flowering signals (SUPPRESSER OF OVEREXPRESSION OF CO1: SOC1, LEAFY: LFY, FLOWERING Locus T: FT, CONSTANCE: CO) from both reference sequences, and very similar found in other species. Conclusions The collected ORFs will be useful as reference sequences for molecular breeding of Japanese and Kuril larches, and also for clarifying the evolution of the conifer genome and investigating functional genomics.